Religious feelings in early and late adulthood - Tatala, Małgorzata (Journal of beliefs and values, 2026)
The aim of the study was to compare different phases of adulthood in terms of religious feelings. To achieve this objective, semantic subgroups derived from expressions of religious feelings encompassed positive and negative qualities, situational context, and regulatory strategies. This process was rooted in Walesa’s cognitive-developmental theory of integral religious development. Under positive qualities, the subcategories included reflexivity, multiple feelings, trust, joy, and love. Negative qualities yielded subcategories of anger, reflexivity, lack of negative feelings, transformation, grief, and multiple feelings. The situational context subcategory was defined by intellectual evaluation, religious practices, and engagement in religious situations. Regulatory strategies encompassed subcategories related to secular and religious life issues, as well as orientation towards eternity. The study included 160 Catholics, with 80 in early adulthood and 80 in late adulthood. Analyses revealed significant differences between these groups across all categories. Early adulthood featured diverse, multifaceted religious feelings, while late adulthood exhibited more uniform, coherent religious feelings, including trust, religious engagement, and orientation towards eternity. Moreover, multilayer perceptron analysis effectively predicted developmental stages based on specific subcategories, shedding light on the dynamic nature of religious feelings across the lifespan and contributing valuable insights to the field of psychology of religion.